Association of Systemic Inflammatory and Immune Indices With Survival in Canine Patients With Oral Melanoma, Treated With Experimental Immunotherapy Alone or Experimental Immunotherapy Plus Metronomic Chemotherapy - Garcia, Jéssica Soares; Nowosh, Victor; López, Rossana Verónica Mendoza; Massoco, Cristina de Oliveira (Frontiers in Veterinary Science, 2022)
Analysis of the expression of inflammatory markers in human patients with cancer before starting treatment may predict outcomes and prognosis; however, there are a few relevant studies in veterinary medicine. This study aimed to evaluate inflammatory indices (neutrophil-lymphocyte ratio [NRL], platelet-lymphocyte ratio [PLR], monocyte-lymphocyte ratio [MLR], systemic immune-inflammation index [SII], C-reactive-protein-albumin ratio [CRP/ALB]), lactate dehydrogenase [LDH], frequency of blood lymphocyte subsets (CD4+, CD8+, Treg and CD4/CD8 ratio) and frequency of blood myeloid-derived suppressor cells (monocytic [M]-MDSCs and granulocytic [PMN]-MDSCs) before treatment with autologous antitumor vaccine alone or plus metronomic chemotherapy (MC) to predict response and prognosis. Blood samples from 25 dogs with oral melanoma treated with autologous antitumor vaccine were collected before surgery, and nine dogs received MC plus vaccine. There were no statistical differences in the progression-free survival (PFS) or overall survival (OS) of patients who received the vaccine plus MC. In addition to the clinical stage, the CRP/ALB ratio and blood circulating Tregs in the univariate analysis showed an association with PFS and OS, and thus were selected for multivariable analysis. CRP/ALB ratio was associated with PFS (hazard ratio [HR], 1.1; confidence interval [CI],1.01.1; p = 0.017) and OS (HR, 1; 95% CI, 1.01.1; p = 0.023). Similarly, Treg was associated with PFS (HR, 1.6; 95% CI, 1.22.1; p = 0.001) and OS (HR, 1.6; 95% CI, 1.22.1; p = 0.001). Furthermore, the CRP/ALB ratio established a cut-off point of 1.9 (by the receiver operating characteristic curve), and canine patients with values higher than 1.9 showed worse PFS and OS, indicating the impact of preoperative CRP/ALB ratio on the PFS and OS of dogs with oral melanoma. The CRP/ALB ratio and frequency of circulating Tregs are potential prognostic factors in dogs with oral melanoma.